Optimalisasi Postur Tubuh melalui Edukasi untuk Mencegah Skoliosis pada Siswa Sekolah Dasar Negeri 3 Tilongkabila - Serly - Daud; Jesica - Mulyadi; Tinah - Tan (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
Scoliosis remains a major musculoskeletal health problem among children and adolescents, particularly during periods of rapid growth. This study aimed to evaluate the effectiveness of a school-based scoliosis screening and health education program conducted at State Elementary School 03 Tilongkabila, Bone Bolango Regency. The program involved health education sessions and scoliosis screening using the Adam’s Forward Bend Test among students in grades 4–6 aged 10–12 years, with a total of 50 participants.The results showed that 3 students (6%) were identified with scoliosis and 5 students (10%) were classified as suspected scoliosis cases. Evaluation using pre-test and post-test questionnaires demonstrated a 45% increase in students’ knowledge after the health education intervention. These findings indicate that combining health education with early screening is effective in improving awareness and facilitating early detection of scoliosis among school-aged children.In conclusion, school-based scoliosis screening integrated with health education is an effective preventive strategy to promote early diagnosis, increase health awareness, and support timely intervention, thereby reducing the risk of scoliosis progression in children.